Regulatory context and main discussions on the Code of Conduct for Arbitrators in investment arbitration - Gómez-Moreno, Juan Pablo (2025)
This research article analyzes the ethical dimension of the investment dispute resolution system and its regulation through a code of conduct. It highlights the importance of addressing ethical issues to strengthen the credibility of the system and discusses the development of regulatory efforts. It also explores the criticisms and challenges surrounding this initiative, highlighting the debates on the contents and scope of the proposed ethical standards. Finally, it compares the multilateral approach with other regulatory standards and examines the arguments for and against these ethical issues, which are relevant in international investment arbitration.